The dawn of industrial agriculture in Iowa : anthropology, literature, and history - Durrenberger, E. Paul, 1943- (University Press of Colorado, 2021)
"Recounts the capitalist transformation of Iowa's family farms into today's agricultural industry through the lives and writings of Iowa novelist Paul Corey and poet Ruth Lechlitner. This anthropological biography analyzes their writing and correspondence to offer a perspective on an era (1925-1947) that saw financial collapse, rise of the Soviet Union, and rise and defeat of fascism"--